Operation Management : An Integrated Approach - Reid, R Dan (Wiley, 2005)
Includes Introduction to Operation Management; Operations Strategy and Competitiveness; Product Design and Process Selection; E-Commerce and Supply Chain Management; Total Quality Management; Statistical Quality Control; Capacity Planning and Facility Design; and Project Management.